2007
DOI: 10.1016/j.seizure.2006.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Seizures during treatment of Vitamin B12 deficiency

Abstract: Epileptic seizures during infancy have a wide variety of clinical presentations and the outcome differs according to the etiology. Among the benign and rare causes of infantile seizures, Vitamin B12 deficiency has been encountered. Common symptoms of Vitamin B12 deficiency in infants include megaloblastic anemia, feeding difficulties, developmental delay, microcephaly, failure to thrive, hypotonia, lethargy, irritability, involuntary movements, seizures and cerebral atrophy. Involuntary movements and seizures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 19 publications
0
41
0
3
Order By: Relevance
“…Cortical atrophy, thinning of the corpus callosum, and retarded myelination have been reported as neuroradiological imaging findings in patients with vitamin B12 deficiency [35,36]. In the present study 4 patients developed involuntary movements during vitamin B12 treatment; it has been reported that such movements rarely occur during vitamin B12 treatment [37,38], although its mechanism is not fully known.…”
Section: Discussionmentioning
confidence: 45%
“…Cortical atrophy, thinning of the corpus callosum, and retarded myelination have been reported as neuroradiological imaging findings in patients with vitamin B12 deficiency [35,36]. In the present study 4 patients developed involuntary movements during vitamin B12 treatment; it has been reported that such movements rarely occur during vitamin B12 treatment [37,38], although its mechanism is not fully known.…”
Section: Discussionmentioning
confidence: 45%
“…Although it has been proposed that hyperglycinemia is responsible for the involuntary movement observed in response to vitamin B12 treatment [7], it was also reported that glycine levels were normal [11]. It was reported that EEG results in patients with seizures due to vitamin B12 deficiency were abnormal, whereas normal EEG results were observed in patients with tremors and myoclonus [1,12,13,16]. As such, it was reported that use of antiepileptics was unnecessary and useless in patients with involuntary movements [1,10,16].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that EEG results in patients with seizures due to vitamin B12 deficiency were abnormal, whereas normal EEG results were observed in patients with tremors and myoclonus [1,12,13,16]. As such, it was reported that use of antiepileptics was unnecessary and useless in patients with involuntary movements [1,10,16]. It is thought that involuntary movements is self-restricted and there is no consensus on the use of antiepileptic treatment [7,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В статье G. Benbir и соавт. (2005) описаны 3 случая появления эпилептических приступов у детей после заместитель-ного введения витамина В 12 [4]. В этих клинических наблюдениях помимо задержки развития разной сте-пени тяжести у детей в период терапии витамином В 12 регистрировались эпилептические приступы по типу миоклонических и клонических, сопровождавшиеся наличием иктальных и интериктальных региональных или мультирегиональных эпилептиформных измене-ний на электроэнцефалограмме (ЭЭГ) вплоть до эпи-лептического статуса.…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified